Bad boys on board - Foster, Lori; Kauffman, Donna; Warren, Nancy (New York : Brava Books, 2003)
Presents three short novels in which cop Sam Watson is attracted to the alluring Ariel, Callie Montgomery is trapped in an elevator with her boss's client, and the kiss of Nell Tennant is all an amnesia patient remembers.
A fast ride / by Nancy Warren
Keywords: Man-woman relationships -- Fiction; Erotic fiction